Implementasi Metode Prototype Dalam Perancangan Sistem Stock Opname Gudang Berbasis Android Pada PT Petra Sejahtera Abadi - Arfayruz Febrynur Hafidz; Khaerul Oktafiansyah; Rafky Ferdian Algiffari; Saprudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
This research discusses the implementation of the Prototype method in designing an Android-based warehouse Stock Opname system at PT Petra Sejahtera Abadi. This system is designed to address the issues of the manual Stock Opname process, which is time-consuming, lacks data integration, and carries the risk of recording errors. The Prototype method was used through the stages of requirement gathering, system design, Prototype creation, evaluation, and testing. Tools such as Android Studio, Firebase, and UML diagrams (Activity Diagram, Usecase diagram, Logical Record Structure) are used to design the user interface, workflow, and database structure. The system integrates user authentication features, daily stock data input, report validation by supervisors, as well as daily and monthly report visualization. The test results show that the system is capable of speeding up the Stock Opname process, improving data accuracy, and providing real-time information access. This research shows that the Android and cloud-based system can improve the efficiency and accuracy of stock management through a Prototype method that effectively adjusts the system to user needs.